U.S. Investment Since the Tax Cuts and Jobs Act of 2017 - Kopp, Emanuel; Leigh, Daniel; Mursula, Susanna; Tambunlertchai, Suchanan (Washington, D.C. : International Monetary Fund, 2019)
There is no consensus on how strongly the Tax Cuts and Jobs Act (TCJA) has stimulated U.S. private fixed investment. Some argue that the business tax provisions spurred investment by cutting the cost of capital. Others see the TCJA primarily as a windfall for shareholders. We find that U.S. business investment since 2017 has grown strongly compared to pre-TCJA forecasts and that the overriding factor driving it has been the strength of expected aggregate demand. Investment has, so far, fallen short of predictions based on the postwar relation with tax cuts. Model simulations and firm-level data suggest that much of this weaker response reflects a lower sensitivity of investment to tax policy changes in the current environment of greater corporate market power. Economic policy uncertainty in 2018 played a relatively small role in dampening investment growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet